Strategy and Culture Alignment by Means of an Organizational Model at PT Pos Indonesia Rural Logistic Project - Wismakumara, Ratri Vibhuti Widyasari; Welly, John (The Indonesian Journal of Business Administration, 2012)
PT Pos Indonesia is going to develop a new project in order to reposition their current core business, called The Rural Logistic Project. This project will integrate all of the PT Pos Indonesia core business. One of the thing that might support The Rural Logistic Project performance is the culture transformation. Here, by using the organizational model which is the 7-S Framework, it can be defined what type of culture that will fit The Rural Logistic Project. Other tools which also help to measure the identification of the culture are the strategy map and the OCAI. The tools giving the result that the suitable culture is the Market culture. There are also several additional values that can be combine with the existing corporate values which is the CINTA POS.Â  Keywords : culture, business reposition, organizational model, PT Pos Indonesia, rural logistic project